PENGARUH PENCANTUMAN SALVINIA MOLESTA PADA KECERNAAN, CARCASS DAN LIMFOID ORGAN BROILER - Freddy Gena, L. D. Mahfudz, Sumarsono (AGROMEDIA: Berkala Ilmiah Ilmu-ilmu Pertanian, 2015)
ABSTRACT The objective of this study was to substitute soybean meal with Salvinia molesta in broiler diets and observed the following parameters; carcass, breast muscle, abdominal fat, crude protein digestibility, spleen and bursa of fabricius. A total of 100, 15 days of age Lohman strain broilers with initial mean body weight of ±773.83 g were used in this experiment. The experimental design was Completely Randomized Design (CRD) with 4 dietary treatments consisted of Salvinia molesta meal as follows; T0 = control diet, T1 = 6% Salvinia molesta added, T2 = 12% Salvinia molesta added and T3 = 18% Salvinia molesta added. The treatments were replicated five times with five chicks per experimental unit. Feed and water was offered ad libitum from day 15 to 42 and the chicks were vaccinated against Newcastle Disease and Gumboro at age 4 and 15 days old. The data was analyzed using analysis of variance (ANOVA) and F-test with the aid of statistics analytical program (SPSS, version 16) and for mean comparison Duncan Multiple Range Test (DMRT) was applied after significant treatment difference (P